Space Balls Revisited: Stereological Estimates of Length With Virtual Isotropic Surface Probes - West, Mark J. (Frontiers in Neuroanatomy, 2018)
The space ball probe was fully described in the literature 15 years ago by Mouton et al. (2002). Since then, it has been used in a number of studies in the nervous system that focus on axon, dendrite, and capillary length. The length of structural parameters in tissues reflect functional aspects of the tissues. Here, some of the various applications of this methodology will be presented, along with a review of the salient features of the methodology that has resulted in new wave of quantitative morphological studies of length in the nervous system. The validity of the method is discussed in view of its widespread use along with insights into the problems associated with its application to histological tissue and future techniques for applying space balls.